Perbandingan Intensitas Pewarnaan Ekstrak Buah Terung Belanda (Solanum betaceum Cav) dengan Disclosing Solution Sebagai Bahan Identifikasi Plak Gigi - Adhitya Oktapraja; Murniwati Murniwati; Kosno Suprianto (Andalas Dental Journal, 2021)
Background: The dental plaque becomes the main etiology of many hard and soft dental tissue’s problem. The dental plaque has a similar color with the teeth, it cannot be seen without a coloring agent. There are two types of coloring used, namely synthetic dyes and natural dyes. Anthocyanin is a natural coloring found in tamarillo that can be used to identify the dental plaque. Methods: This study used a quasi-experimental method with post-test only one group design with independent t-test. The study was conducted in February 2019. Twelve samples were selected based on the inclusion and exclusion criteria. The samples were given two times plaque examination, then the result were recorded in RKP (Plaque Control Record) form. The data analyzed by using SPSS. Results: The average score of plaque control with disclosing solution was 26.93%, while the plaque control score with tamarillo extract was 20.02%. Bivariate test results obtained p=0.037 (p<0.05) which means there is a significant difference between the plaque control scores using disclosing solution and plaque control with tamarillo extract. Conclusion: Tamarillo extract cannot be used in the identification of dental plaque, because the color intensity is not as good as the use of disclosing solution.